Introduction to sustainability as a transversal competence in higher education - Ramalho, V.; Belchior-Rocha, H.; Roseta-Palma, C. (Edulearn 2022 - 14th annual International Conference on Education and New Learning Technologies, 2022)
Sustainability in higher education institutions is little discussed, but there is a large amount of literature that mentions its importance for the awareness of all those who frequent their spaces, whether they are teachers, employees, or students. The understanding, by the human being, of the complex nature of the environment and the perception of the interdependence of the environmental elements in space and time is crucial and, for this reason, the education in this area must be accessible to all and at all levels of education, not matter what subject area. Since 2019, in the Soft Skills Lab of a public university was created a curricular unit called - Introduction to Sustainability, with the aim that students and everyone involved with the environment in a higher education institution can be fully aware of what it means to develop sustainability actions, both in the environment and in the very contents of the various courses developed in the institution they are a part of. This exploratory study aims to disseminate this experience with the 1st cycle students and also with workshops made with the employees as a practice that can be replicate in other institutions. The evaluation was made through the process of pedagogical monitoring students make every semester and in the case of the employees through a evaluation survey. It was very motivating to see the commitment that both students and employees have started to show in their daily behavior and even the creative suggestions for their participation in this matter.